EVALUASI PELAKSANAAN PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) PADA MADRASAH ALIYAH NEGERI 2 KOTA PALU - Harsono, Harsono; Tjaya, Abu; Mustari, Hasanuddin (Katalogis, 2020)
The purpose of this study was to determine the evaluation of the implementation of the School Operational Assistance Program (Bos) at State 2 Madrasah Aliyah in Palu City. The foundation of the theory used is William N. Dunn (2003) which states that there are six factors in evaluating the implementation of the program, namely effectiveness, efficiency, adequacy, alignment, responsiveness, and accuracy. This type of research is Qualitative Descriptive which seeks to interpret and interpret data that is pleasing to the facts, using purposive methods, data cursing and discussion with a qualitative analysis approach to collecting data and materials through observation and interviews with the number of 5 informants. Based on the results of the discussion that the Evaluation of the Implementation of the School Operational Assistance Program (BOS) at the State 2 Madrasah Aliyah in City of Palu for effectiveness, efficiency, alignment, responsiveness, and accuracy has been running optimally. However, for the adequacy factor it has not run optimally because the BOS budget is considered to be insufficient or insufficient to finance all school operational costs in order to improve the quality of education services to the community.